Biotransformation of ω-fatty acid – in search of erectile dysfunction treatments - Omar, Muhammad Nor; Shaban, Norhayati; Zuberdi, Ahmad Muzammil (2010)
Biotransformation can be defined as an application that utilized natural and recombinant organisms’ enzymes secreted by yeast, fungi and bacteria or whole cells as biocatalyst in synthesis of organic compound. Therefore, Pseudomonas aeruginosa bacterium has been chosen to be the biocatalyst for biotransformation of ω fatty acids extracted from Malaysian catfish (Clarias batrachus), giant snakehead fish (Channa micropeltes) and giant mudskipper (Periophthalmodon schlosseri) which emphasized on bioconversion of arachidonic acid (C20:4 ω6). The lipid from freeze-dried catfish flesh was extracted by a modified Folch method using the chloroform and methanol solutions. Then, the crude lipid extract was added to the bacterial culture and incubated for 4 days. After conversion, the biotransformation products were analyzed by using gas chromatography and mass spectrometer (GC-MS). The analytical result showed that several fatty acids and cholesterol were found in the product. However, the fatty acids and cholesterol contents before and after biotransformation were different. The cholesterol content increased while ω-fatty acid contents decreased after biotransformation process. It can be concluded that the bacterial cells had oxidized the ω-fatty acids to yield precursors which later can be utilized as starting materials for biosynthesis of cholesterol.